THE EFFECTIVENESS OF USING QUIZIZZ TO ENHANCE STUDENTS’ LEARNING MOTIVATION AT SMK MUHAMMADIYAH 4 KALISAT - Yessy Putri Wulandari; Syahrul Mubaroq; Dina Merdeka Citraningrum (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to determine the effectiveness of using Quizizz in increasing student learning motivation at SMK Muhammadiyah 4 Kalisat. The research sample consisted of 20 students in class X DKV 1. The type of research was the development of learning media with descriptive qualitative data analysis, using the model of Matthew B. Miles and A. Michael Huberman (Miles & Huberman, 1994). The results of the data analysis show that the majority of students stated that they felt more enthusiastic about learning and felt challenged when using Quizizz as a learning medium. These findings indicate that Quizizz can be used to increase student learning motivation at SMK Muhammadiyah 4 Kalisat.